Hashimoto Encephalopathy with an Unusual Presentation of Status Epilepticus Seizures: A Case Report - Masoume NAZERI; Amin ABOLHASANI FOROUGHI; Hora HEIDARI; Sarvin SAJADIANFARD; Tannaz EGHBALI; Peyman ARASTEH (Tehran University of Medical Sciences, 2016)
A 33 yr old man, previously diagnosed with hypothyroidism, presented with decreased level of consciousness and generalized tonic-clonic (GTC) seizure to Namazi hospital, Shiraz, Iran, during April 2015. The patient later referred with another episode of seizure like attack for which he received phenytoin, carbamazepine and levothyroxine and was discharged. During his last admission, the patient was admitted with chief complaints of decreased consciousness and four GTC attacks. On admission, the patients had aphasia, ataxia, loss of verbal communication, eye contact and complete loss of obedience. Thyroid function tests showed low levels of T3 and T4 with high levels of thyroid stimulating hormone. Other blood tests were all either normal or slightly abnormal. Lumbar puncture and CSF analysis had a high titer of Anti-TPO antibodies. With high suspicion of Hashimoto encephalopathy, pulsed methyl prednisolone (10 mg) was administered, however the patient showed little improvement. Therefore, plasmaphresis was started, to which the patient showed dramatic response.   Keywords: Hashimoto encephalopathy, Epilepsy, Iran